Regulation of Exocyst Function in Pollen Tube Growth by Phosphorylation of Exocyst Subunit EXO70C2 - Saccomanno, Antonietta; Potocký, Martin; Pejchar, Přemysl; Hála, Michal; Shikata, Hiromasa; Schwechheimer, Claus; Žárský, Viktor (Frontiers in Plant Science, 2021)
Exocyst is a heterooctameric protein complex crucial for the tethering of secretory vesicles to the plasma membrane during exocytosis. Compared to other eukaryotes, exocyst subunit EXO70 is represented by many isoforms in land plants whose cell biological and biological roles, as well as modes of regulation remain largely unknown. Here, we present data on the phospho-regulation of exocyst isoform EXO70C2, which we previously identified as a putative negative regulator of exocyst function in pollen tube growth. A comprehensive phosphoproteomic analysis revealed phosphorylation of EXO70C2 at multiple sites. We have now performed localization and functional studies of phospho-dead and phospho-mimetic variants of Arabidopsis EXO70C2 in transiently transformed tobacco pollen tubes and stably transformed Arabidopsis wild-type and exo70C2 mutant plants. Our data reveal a dose-dependent effect of AtEXO70C2 overexpression on pollen tube growth rate and cellular architecture. We show that changes of the AtEXO70C2 phosphorylation status lead to distinct outcomes in wild type and exo70c2 mutant cells, suggesting a complex regulatory pattern. On the other side, phosphorylation does not affect the cytoplasmic localization of AtEXO70C2 or its interaction with putative secretion inhibitor ROH1 in the yeast two-hybrid system.